AKIBAT KEKOSONGAN HUKUM TERHADAP NON-FUNGIBLE TOKEN SEBAGAI PELANGGARAN HAK KEKAYAAN INTELEKTUAL - Gabriella Ivana (JURNAL USM LAW REVIEW, 2022)
This study aims to analyze the impact of a legal vacuum on digital art in NFT (Non-Fungible Token) as a violation of intellectual property rights and find out how the current regulation regarding digital art in NFT is viewed from Intellectual Property Rights. The era is growing, presenting the development of technological sophistication which is one of the things that is most needed by humans. One form of this technological sophistication is the internet and smartphones. Humans can communicate, buy and sell transactions, and so on only through the internet. In terms of buying and selling transactions, the emergence of NFT as a digital asset has become a trendsetter favored by many parties because the presence of NFT can be utilized in the arts, business, and entertainment industries. The research method used in this research is normative juridical research with a case study approach and legislation. The results of this study conclude that the legal vacuum of digital art in NFT triggers the occurrence of violations that can harm certain individuals such as plagiarism, theft of works, and even forgery and fraud. It is necessary to add regulations regarding all activities within the NFT itself, including legal sanctions. This study seeks to explain all the possibilities of criminal acts that may occur and their settlements based on the Law relating to Intellectual Property Rights.